Sensitivities of Bottom Stress Estimation to Sediment Stratification in a Tidal Coastal Bottom Boundary Layer - Yun Peng; Qian Yu; Yunwei Wang; Qingguang Zhu; Ya Ping Wang (Journal of Marine Science and Engineering, 2020)
The bottom friction velocity (U*), which controls seabed erosion and deposition, plays a critical role in sediment transport in tidal coastal bottom boundary layers. Approaches have been proposed to calculate U*, including the log profile (LP) estimation, the direct covariance (COV) measurement, and the turbulent kinetic energy (TKE) method. However, the LP method assumes homogeneous flow and the effects of stratification need to be taken into account. Here, field investigations of hydrodynamics and sediment dynamics were carried out on the Jiangsu Coast, China. Two acoustic Doppler velocimeters (ADV) velocity measurements at 0.2 and 1 m above the seabed have been used to estimate U*, based on the aforementioned three methods. The COV and TKE methods provided reasonable estimations of U*, while a pronounced overestimation was identified when using the LP method. This overestimation can be attributed to the stratification effects associated with the vertical suspended sediment concentration (SSC) gradient near the bottom. Then, three models were utilized to correct the overestimation, in which the gradient/flux Richardson number was modified with empirical constants α, β, and A to parameterize the stratification effects in the logarithmic velocity distribution. The values of α, β, and A derived from the observation are smaller than the results from previous investigations. These modified logarithmic velocity distribution models can be applied in numerical simulations when sediment stratification is important.